Palm oil γ-tocotrienol and α-tocopherol act as potent inducers in the immune response of mouse splenocytes in vitro / Narimah Abdul Hamid Hasani, Khalid bin Abdul Kadir and Wan Zurinah Wan Ngah - Abdul Hamid Hasani, Narimah; Abdul Kadir, Khalid; Wan Ngah, Wan Zurinah (Research Management Institute (RMI), 2011)
Vitamin E may have anti carcinogenesis effect in human and animal models via the mechanism of cell cycle arrest and enhancement of immune system. The cell-mediated immune inducing properties of palm oil vitamin E, for example, γ-tocotrienol and α-tocopherol, were investigated by measuring the mitogenesis response of splenocytes, extracted from normal male Mus musculus to splenic T-lymphocytes mitogens, phytohemagglutinin (PHA; 0.25 μg/mL) and concanavalin A (Con A; 1.0 μg/mL); and B-lymphocytes mitogen i.e., lipopolysaccharide (LPS; 1.0 μg/mL). Both γ-tocotrienol and α-tocopherol enhanced the cell proliferation of mitogen untreated splenocytes as determined by 5-Bromo-2'-deoxy-uridine (BrdU) detection method. Both compounds also enhanced the T-lymphocytes response to PHA and Con A, as well as B-lymphocytes responses to LPS at all concentration used (0-300 μM). γ-Tocotrienol was observed to affect cell proliferation more than α-tocopherol. The uptake of γ-tocotrienol and α-tocopherol into the splenocytes was determined by high performance liquid chromatography (HPLC). γ-Tocotrienol was absorbed into the cells at markedly higher levels than α-tocopherol with the ratio of 4.8 : 1 (p<0.01, n=4) at 300 μM of treatment. This may be the reason of the higher proliferation affect of γ-tocotrienol as compared to α-tocopherol. In conclusion, we are of the opinion that palm oil γ-tocotrienol and α-tocopherol are able to synergistically influence splenocytes proliferation thus enhancing the cellmediated immune system.